An investigation into the causes, impacts and measures to deal with diatom bloom in Vartry Reservoir - SHI, YUNHONG (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2019)
In Ireland, there are more than 12,000 lakes and lakes and reservoirs are the main source of drinking water for two million people. Consisting of upper lake and lower lake, Vartry Reservoir is a key drinking water source in Ireland. It serves more than 220,000 customers and the supply areas stretching from Roundwood, through north Wicklow up to south Dublin. However, since 2013 Asterionella dominated diatom bloom has been occurring in spring each year which has led to serious clogging of the slow sand filters in Vartry water treatment plant. As a result, the treatment capacity through the plant decreased significantly from 75 million litres per day to 40 million litres per day, creating a potential water shortage. In this study, in addition to collecting and analysing historical water quality and ecology data, a three-year monitoring programme (from 2016 to 2018) and a series of laboratory experiments were carried out to (1) analyse the diatom growth trend in Vartry Reservoir; (2) understand the change of nutrient concentrations in Vartry Reservoir; (3) investigate the causes of diatom bloom and (4) recommend the measures to effectively mitigate diatom bloom. In Vartry Reservoir, diatom bloom occurred in spring and no obvious bloom was observed in autumn or winter. The diatom species included Melosira, Tabellaria, Asterionella, Synedra and Navicular. In the lower lake from 1996 to 2018, Asterionella, Melosira, Synedra and Tabellaria dominated the diatom assemblages for 12 years, 7 years, 1 year and 1 year, respectively. Diatom growth in the lower lake from 1996 to 2012 was stable and the maximum diatom number was lower than 1000 counts/mL. From 2013 to 2016, diatom bloom in the lower lake was problematic and the peak diatom values was about 2000 counts/mL. The highest diatom number in the upper lake in 2017 and 2018 was 4940 counts/mL and 1762 counts/mL, respectively, which were much higher than that observed in the lower lake with the values of 821 counts/mL and 1120 counts/mL. Nutrient monitoring showed that nutrient concentrations in the feeding rivers were higher than that in the reservoir. No diatom growth was observed in the feeding rivers. Feeding rivers with high silica concentrations (about 9 mg/L) flowing into the reservoir were silica sources in Vartry Reservoir. Every year, the silica concentrations in the reservoir started to decrease when diatom bloom started. It reduced to the annual minimum values when diatom bloom completed. The silica concentrations then increased continuously until the next diatom bloom period. The soluble reactive phosphorus (SRP) concentrations in the reservoir were lower than 9 μg/L in lower lake and 12 μg/L in the upper lake. Generally, the peak SRP concentration appeared before diatom bloom. The nitrogen concentration in the reservoir peaked at the beginning of diatom growth i.e. in spring, and then decreased to the lowest points in autumn. Then it increased again until the beginning of next diatom bloom period. No significant increasing trend of nutrient concentrations in the reservoir were observed during the study period. Nutrient and zooplankton were two major reasons for diatom bloom. The silica concentration in Vartry Reservoir was sufficient for diatom bloom. The soluble relative phosphorus could be a factor that leads to diatom bloom in Vartry Reservoir. The concentration of SRP determined the magnitude of diatom bloom. In the upper lake, the average SRP concentrations before diatom bloom season were 1.15 ug/L, 3.58 ug/L and 1.18 ug/L in 2016, 2017 and 2018, respectively, accordingly, the peak diatom concentrations were 2000 counts/mL, 4,900 counts/mL and 1762 counts/mL. The high diatom concentration in 2017 could be due to the relatively high SRP concentration. The low zooplankton number was another factor that could influence diatom growth in Vartry Reservoir. The dominant zooplankton species in Vartry Reservoir were Rotifer, Daphnia and Copepods. Zooplankton predation could reduce the diatom concentrations in the reservoir. The ratio of diatom number and zooplankton number (food to predator ratio) determined the extent of zooplankton limiting the diatom growth. Laboratory experiments indicated that diatom growth was fully inhibited when the diatom/zooplankton ratio was lower than 14.4 ?103. When the ratio of diatom to zooplankton number was higher than 40.9?103, the influence of predation on diatom number was negligible. However, in Vartry Reservoir, the ratio of diatom number to zooplankton number was always higher than 40.9?103, indicating that the low zooplankton population could contribute to diatom algae bloom in Vartry Reservoir. In Vartry Reservoir, the following measures could be considered to deal with diatom bloom. The limitation of nutrient especially phosphorus entering the reservoir was meaningful for the long-term protection of water quality in Vartry Reservoir. Increasing the number of zooplanktons in the reservoir could effectively control the diatom growth. In Vartry water treatment plant, coagulation and filtration could be considered for the removal of diatom before the raw water entering the slow sand filters. This study provided diatom bloom pattern of Vartry Reservoir in 23 years and identified the factors that control diatom algae populations as well as the effective measures to deal with diatom issue. These results not only benefit the management of water supply in Ireland with more than 70 mesotrophic lakes used as water supply sources, but also deepen the understanding of diatom bloom causes and control, which is very important to tackle with the more and more frequent diatom bloom cases worldwide.
APPROVED
Keywords: Diatom, Asterionella, Nutrients, Silica, Soluble relative phosphorus, Zooplankton